Iran's national ICT educational plan and factors affecting Iranian principals' use of ICT - Afshari, Mojgan; Abu Bakar, Kamariah; Abu Samah, Bahaman; Foo, Say Fooi; Wong, Su Luan (Malaysian Educational Technology Association, 2007)
During the past decade there has been an exponential growth in the use of ICT which has made pervasive impacts both on society and on daily lives. Thus, it is not surprising to find increasing interest, attention and investment being put into the use of ICT in education all over the world (Albirini, 2006). Not to be left out, Iran, a developing country is currently pursuing the technological track in education. Iran intends to transform its educational system to get sustained, productivity growth, which will be achieved only with a technologically literate, critically thinking work force prepared to participate fully in the global economy of the 21st century (Jahangard, 2003). With respect to this vision, in 2003, one important ICT agenda was approved by the highest authority in administrative affairs in Iran in order to promote and improve services of governmental organizations based on ICT. However, little is known about this national ICT educational plan in Iran and the factors that can influence Iranian school leaders’ decision to use ICT. This paper, therefore, examines the status of the first and most significant national ICT educational plan based on the recent Iran’s National ICT Agenda (INICTA). It also highlights the aim of INICTA in respect to education. Apart from that, this paper discusses possible factors that can influence Iranian principals’ decision to use ICT for administrative and instructional purposes.